2004
DOI: 10.1042/bj20031825
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary families of peptidase inhibitors

Abstract: The proteins that inhibit peptidases are of great importance in medicine and biotechnology, but there has never been a comprehensive system of classification for them. Some of the terminology currently in use is potentially confusing. In the hope of facilitating the exchange, storage and retrieval of information about this important group of proteins, we now describe a system wherein the inhibitor units of the peptidase inhibitors are assigned to 48 families on the basis of similarities detectable at the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
414
0
32

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 552 publications
(450 citation statements)
references
References 105 publications
4
414
0
32
Order By: Relevance
“…Rawlings et al (25) have identified 13 clans of Laskowski serine protease inhibitors with distinct 3D folds, indicating that the mechanism has evolved many times. At present, however, there are very few examples of inhibition of other protease types by a mechanism in which a peptide segment binds in a substrate-like manner and resists hydrolysis (25). The best-characterized example appears to be Streptomyces metalloproteinase inhibitor (SMPI) (46), but this inhibitor is much more susceptible to hydrolysis than most of the serine protease inhibitors, with a turnover time of Ͻ10 min when bound to thermolysin (46).…”
Section: B Amentioning
confidence: 99%
See 2 more Smart Citations
“…Rawlings et al (25) have identified 13 clans of Laskowski serine protease inhibitors with distinct 3D folds, indicating that the mechanism has evolved many times. At present, however, there are very few examples of inhibition of other protease types by a mechanism in which a peptide segment binds in a substrate-like manner and resists hydrolysis (25). The best-characterized example appears to be Streptomyces metalloproteinase inhibitor (SMPI) (46), but this inhibitor is much more susceptible to hydrolysis than most of the serine protease inhibitors, with a turnover time of Ͻ10 min when bound to thermolysin (46).…”
Section: B Amentioning
confidence: 99%
“…Since then, it has been found that SBTI is one of a very large number of inhibitors, described as ''standard mechanism'' or ''Laskowski mechanism'' inhibitors, that act by binding tightly to the active sites of their targets as a substrate would, but resist hydrolysis for many hours or longer (22)(23)(24)(25). Because the products of hydrolysis remain physically associated, the resynthesis of these inhibitors is an intramolecular reaction and is, therefore, much more favorable than the equivalent intermolecular reaction at modest reactant concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a leucine (leucyl) aminopeptidase (LAP) and a (LAP)-related protein in the genome and secretome is an important finding. LAPs are often viewed as cell maintenance enzymes with critical roles in turnover of peptides (Rawlings et al, 2004). Some LAPs may bind DNA enabling them to serve as transcriptional repressors that control pyrimidine, alginate and cholera toxin biosynthesis, as well as mediate sitespecific recombination events in plasmids and phages (Matsui et al, 2006).…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 99%
“…However, a few members possess two reactive sites that simultaneously bind two protease molecules and are thus termed double-headed inhibitors (15-18). All of these inhibitors are classified into family I3 of peptidase inhibitors (19). Most members are further grouped into subfamily I3A.…”
mentioning
confidence: 99%